2004
DOI: 10.1111/j.1945-5100.2004.tb00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐metasomatism in chondrules in CO3 chondrites: Relationship to parent body thermal metamorphism

Abstract: Sodium-metasomatism in chondrules in CO3 chondrites:Relationship to parent body thermal metamorphism Abstract-We have studied the mineralogy and petrology of mesostases of 783 type I chondrules in seven CO3 chondrites that range in petrologic subtype from 3.0 to 3.7. Chondrule mesostases in the CO chondrite of subtype 3.0 consist mainly of primary glass and plagioclase, while chondrule mesostases in the CO chondrites of higher subtypes (3.2-3.7) contain various amounts of nepheline in addition to glass and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 28 publications
(43 reference statements)
6
44
0
Order By: Relevance
“…Glass has been partially replaced by nepheline. These characteristics are similar to those of the CO3.2 -3.5 chondrites (Tomeoka and Itoh, 2004). CAIs and AOIs.…”
Section: Lithology Asupporting
confidence: 71%
See 2 more Smart Citations
“…Glass has been partially replaced by nepheline. These characteristics are similar to those of the CO3.2 -3.5 chondrites (Tomeoka and Itoh, 2004). CAIs and AOIs.…”
Section: Lithology Asupporting
confidence: 71%
“…The mineralogy of the chondrules, CAIs, AOIs, and matrix are also consistent with this classification (e.g., Scott and Jones, 1990;Kojima et al, 1995;Rubin, 1998;Tomeoka and Itoh, 2004). However, lithology A and lithology B show minor, but significant differences in mineralogy.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The black and white lines are probably attributable, respectively, to nepheline and FeS, even though measuring pure chemical compositions of these lines is difficult because the excitation volume by the electron beam was expanded to about 2-3 µm even though the electron beam diameter was confined to less than 0.1 µm. Similar black lines were found in a chondrule of a CO3 chondrite by Tomeoka and Itoh (2004). They suggested that the lines were generated by replacement of plagioclase by nepheline through the sodiummetasomatism because of parent body thermal metamorphism.…”
Section: Grain Size Of Plagioclase and Possible Fe-alkali Metasomaticsupporting
confidence: 52%
“…There is also no reason to assume that chondrites classified as type 3 have escaped aqueous alteration. Hydrous minerals are well known in type 3 chondrites like Semarkona (e.g., Hutchison et al 1987), and there is evidence for aqueous alteration in CO chondrites (e.g., Rubin 1998;Greenwood and Franchi 2004;Tomeoka and Itoh 2004).…”
Section: Revision Of the Petrologic Subtypesmentioning
confidence: 99%